Decomposition of UV induced ESR spectra in modern and fossil dental enamel fragments - Grün, R.; Joannes-Boyau, R. (Ancient TL, 2010)
Using an automated simulated annealing (SA) procedure, spectrum decomposition on angular measurements of tooth enamel fragments shows that UV irradiation of modern human and fossil bovid samples results in distinctively different ESR spectra. In the fossil sample, UV irradiation generates qualitatively identical spectra to natural. The amounts of non-oriented CO2 - radicals in the modern and fossil samples are about 35% and 9%, respectively. The two oriented CO2 - radicals, R1 and R2, attributed to orthorhombic and axial types, show a ratio of 64:36 in the modern and 34:66 in the fossil sample. R1 is also observed in the natural fossil sample, while the axial type was either absent or too small to be identified in a -irradiated fossil sample. We could not observe a measurable UV induced signal after 7 months of sunlight and laboratory light expos ure, respectively. The clear difference between  and UV induced signal raises the possibility of using UV lights for dating protocols.